The Association Between Treatment Failure of Bacterial Vaginosis with Metronidazole and the Incidence of the Maternal–Perinatal Composite Index - Kennedy Winartan; I Gusti Ayu Sri Anjani; Anak Agung Raka Budayasa (Warmadewa University, 2026)
There is high incidence of Bacterial vaginosis (BV) in pregnancy and increasing rate of treatment failure with metronidazole, the drug of choise in BV in pregnancy. The occurrence of bacterial vaginosis in pregnancy results in morbidity and complications for both the mother and the fetus, especially in untreated cases or cases of treatment failure. This study aims to determine the association between treatment failure and the incidence of the maternal–perinatal composite index (preterm labour, PPROM, low birth weight ). This is a cohort study, conducted at Sanjiwani Hospital, Gianyar, from September 2024 to April 2025. involving 52 pregnant less than 20 weeks diagnosed with BV who received metronidazole therapy, divided into two groups, 26 pregnant woman with successful treatment and 26 pregnant woman with treatment failure.The results demonstrated that pregnant women with treatment failure of bacterial vaginosis had a 5.33-fold higher risk of maternal–perinatal complications (OR 5.33; 95% CI = 1.008–28.209; p = 0.049) compared to those with successful treatment.